1990
DOI: 10.1002/tox.2540050105
|View full text |Cite
|
Sign up to set email alerts
|

Role of envelopes of gram‐negative bacteria in cadmium binding and toxicity

Abstract: Whole cells, mureinoplasts, and protoplasts of gram-negative bacteria were used in cadmium biosorption and toxicity determinations. It was shown that whole cells of Pseudomom fluorescens bind less metal than other bacterial forms, suggesting the outer membrane acts as a barrier toward metals. Such a role was confirmed by toxicity measurements showing a lower toxic effect of cadmium in the presence of the outer membrane. Chemically modified bacteria, with carboxyl groups masked, were used to identify the cadmiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…The lack of sensitivity of Gram-negative bacteria towards cadmium (e.g. 15 min EC 50 V. fischeri 36.08 mg Cd/l, [16]) has been reported by many authors [16,24,36] and attributed to the presence of exopolysaccharides on the outer layer of the bacteria membrane, which have been found to adsorb and trap cadmium [36].…”
Section: Sensitivity Of Bacterial Tests -Comparison To D Magnamentioning
confidence: 96%
“…The lack of sensitivity of Gram-negative bacteria towards cadmium (e.g. 15 min EC 50 V. fischeri 36.08 mg Cd/l, [16]) has been reported by many authors [16,24,36] and attributed to the presence of exopolysaccharides on the outer layer of the bacteria membrane, which have been found to adsorb and trap cadmium [36].…”
Section: Sensitivity Of Bacterial Tests -Comparison To D Magnamentioning
confidence: 96%
“…Finally, microorganisms may respond differently to the attacks by heavy metals. The outer membrane of gram-negative bacteria acts passively as a barrier toward metals, as has been shown by Bauda and Block (1990) with cadmium. But other bacteria have adapted to high concentrations of metal ions, acquiring resistances that can be governed by plasmid-encoded mechanisms in both gram-negative and gram-positive bacteria (Kelly and Reanney, 1984;Trevors et al, 1985;Nieto et al, 1987;Schmidt et al, 1991;Tsai et al, 1992).…”
Section: Introductionmentioning
confidence: 98%
“…Whereas, numerous study have reported, Gram-negative bacteria is less sensitive towards Cd 2+ . The outer layer of the bacteria membrane is made of exo-polysaccharides which are able to adsorb and trap Cadmium [ 46 , 47 , 48 ]. Data in the previous study further supported the least metal toxicities of Cd 2+ in this study.…”
Section: Discussionmentioning
confidence: 99%